Liquid Crystal Optics for Applications - Takatoh, Kohki; Mochizuki, Akihiko (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this Special Issue, you will find new directions in the research on liquid crystal applications. To be honest, we were surprised to find 10 papers covering a variety of application areas, with no overlap between them. The only important application without a related article was "display"! This was exactly the situation we hoped for. In this Special Issue, you can find 10 articles discussing the applications of LC devices or LC materials. The applications are liquid crystal on silicon (LCOS) for optical communication, laser processing and wireless optical charging, wavelength selective filters, waveguides, smart windows, LCDs for terahertz waves, LC polymers for polarizing grating and LC material for an ink.We believe that this Special Issue will help researchers focusng on optical devices or LC materials to obtain inspiration for new devices using liquid crystals.